Factors affecting cigarette and alcohol use initiated and quitted from the perspective of university students - Siyez, D. M. (Journal of Dependence, 2008)
Objective: This study aimed to determine the factors that are effective in starting to use cigarettes and alcohol and in quitting smoking, according to university students. Method: The study sample consisted of 396 undergraduate students attending undergraduate programs at Dokuz Eylül University, Buca Faculty of Education. Data collection tools were the Problem Behavior Index, Reasons for Smoking, Reasons for Alcohol Use, and Reasons for Quitting Smoking scales. Frequency distributions were calculated using SPSS 11.0 for data analysis, and chi-square significance tests were conducted. Findings: When the factors that may be effective in starting and quitting smoking, according to university students, were evaluated in order of importance: “It relaxes people when they are stressed” (35.6%) and “It provides pleasure after meals” (31.8%) were among the most important factors that may be effective in starting to smoke, while “It is harmful to health” (87.4%) and “It smells bad” (86.9%) were among the most effective factors in quitting smoking. Factors that may influence the initiation of alcohol use, ranked in order of importance, are "People around you also use alcohol" (65.4%), "It brings people closer together" (47.3%), and "It makes you feel more comfortable in social settings" (43.9%). The findings of the study reveal that the factors influencing smoking and alcohol use and quitting smoking differ significantly based on whether or not they use cigarettes or alcohol. Conclusion: University students pointed to the relaxing effect of alcohol as the most important factor influencing smoking. The most influential factor in alcohol preference is its role in facilitating interaction in social settings. The harmful effects of smoking on health are considered a significant reason for quitting or not smoking.